<h2>
Answer: y = x + 1
</h2>
Step-by-step explanation:
For us to write the equation for this line, we need to (1) find the slope of the line, and (2) use one of the points to write an equation:
The question gives us two points, (3, 4) and (-4,-3), from which we can find the slope and later the equation of the line.
<u>Finding the Slope</u>
The slope of the line (m) = (y₂ - y₁) ÷ (x₂ - x₁)
= (4 - (- 3)) ÷ (3 - (-4))
= 1
<u>Finding the Equation</u>
We can now use the point-slope form (y - y₁) = m(x - x₁)) to write the equation for this line:
⇒ y - (-3) = 1 (x - (-4))
y + 3 = (x + 4)
we could also transform this into the slope-intercept form ( y = mx + c)
since y + 3 = (x + 4)
⇒ y = x + 1
<em>To test my answer, I have included a Desmos Graph that I graphed using the information provided in the question and my answer.</em>